A multi-component reaction for the synthesis of pyrido [1, 2-b] isoquinoline derivatives via the [3 + 2] cycloaddition reaction between alkynes and in situ generated isoquinolinium ylides. Issue 16 (10th April 2019) - Shinde, Sundar S.; Laha, Soumi; Tiwari, Dharmendra K.; Sridhar, B.; Likhar, Pravin R.
Abstract : Metal-free unprecedented [3 + 2] cycloaddition of alkynes and isoquinolinium ylide generated in situ from proline and ninhydrin to pyrido [1, 2- b ] isoquinoline derivatives. Abstract : An efficient and one-pot tandem procedure for the synthesis of fused ethanopyrido [1, 2- b ] isoquinoline derivatives from ninhydrin, proline and alkynes has been developed. This strategy exhibits an unprecedented [3 + 2] cycloaddition reaction between alkynes and isoquinolinium ylide (1, 3 dipole) generated in situ from proline and ninhydrin. This newly developed methodology features simple operation and is metal free. In this methodology overall three new C–C bonds, two C–N bonds, and three new rings are formed in a single step process.